2008
DOI: 10.1002/oa.1009
|View full text |Cite
|
Sign up to set email alerts
|

High performance liquid chromatography (HPLC) in the investigation of gout in palaeopathology

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 10 publications
1
29
1
Order By: Relevance
“…In the individuals from Bromyard and Lincoln the white powders in which the crystals have been found suggest the remains of tophi, and previously we have detected uric acid by high performance liquid chromatography (HPLC) in them (Swinson et al, 2010). In the individual from Lisbon there was no white powder and the crystals were found within bone powder sampled from a gouty articular erosion.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the individuals from Bromyard and Lincoln the white powders in which the crystals have been found suggest the remains of tophi, and previously we have detected uric acid by high performance liquid chromatography (HPLC) in them (Swinson et al, 2010). In the individual from Lisbon there was no white powder and the crystals were found within bone powder sampled from a gouty articular erosion.…”
Section: Discussionmentioning
confidence: 86%
“…In the latter, methods included histology, biochemistry, polarising light microscopy and scanning electron microscopy. A recent study by the authors (Swinson et al, 2010) identified two cases of individuals in which white powder associated with gouty lesions was shown to contain monosodium urate crystals. In addition, recent work undertaken by the authors has identified a case where crystals were found in bone dust extracted from a gouty articular erosion with no white powder (see Fig.…”
Section: Introductionmentioning
confidence: 97%
“…Uric acid accumulation in the blood causes the precipitation of sodium urate crystals that constitute nodules deposited into the soft tissue, known as tophi. These collections, penetrating in the deep bone tissue, cause erosion of bone and cartilage, mostly on the articular surface and close to the margins of the joints, resulting in a destructive, chronic and disabling arthritis, often involving many joints [18,19]. Erosive damage is a late feature of chronic gout, typically occurring 15 years after onset of the disease [20].…”
Section: Differential Diagnosis and Discussionmentioning
confidence: 99%
“…Particularly common are vertebral body compression fractures, extensory fracture of the radial bone distal epiphysis (Colles' fracture) and femoral neck fracture. It is caused by excessive accumulation of uric acid (Ortner 2003;Swinson et al 2010). In the past it was probably one of the most important causes of arthritic joint destruction (Klepinger 1980).…”
Section: Osteoporosismentioning
confidence: 99%